A longitudinal study of incident hypertension and its determinants in Indian adults aged 45 years and older: evidence from nationally representative WHO-SAGE study (2007–2015) - Bhatia, Mrigesh; Dixit, Priyanka; Kumar, Manish; Dwivedi, Laxmi Kant (Frontiers in Cardiovascular Medicine, 2023)
MB, LKD, and PD conceptualised the study. MB, PD, and MK were responsible for writing the original draft. MK and LKD were involved in the formal analysis of the data. All the authors contributed to the editing and verification process and approved the final draft of the manuscript. MB was responsible for funding acquisition.The Indian Council of Medical Research (ICMR) extended the necessary guidelines and ethics approval for undertaking the LASI survey. All methods were carried out in accordance with the relevant guidelines and regulations of ICMR. The survey agencies that conducted the field survey for data collection had obtained prior informed consent from the respondents.